Hepatic toxicity caused by PLGA-microspheres containing usnic acid from the lichen C ladonia substellata (AHTI) during pregnancy in Wistar rats - MARINHO,KETSIA S.N. (2017)
ABSTRACT This study aimed to evaluate the teratogenic and hepatotoxic potential of the usnic acid encapsulated into PLGA-microspheres. In total, 12 female Wistar rats in pregnancy were randomly distributed in the control group (n= 6) that received 1.0 mL of physiological solution and treatment group (n= 6) that received 25 mg/kg of encapsulated usnic acid by oral administration. All females were euthanized at day 20 of pregnancy and their fetuses were removed and analyzed. During the pregnancy was observed a reduction in weight gain. There was no difference in serum transaminases levels analyzed as well as any difference in liver weight in both groups. The histomorphometric analysis of the liver from the treatment group revealed an increase in number of hepatocytes and a decrease in nuclear area of these cells. Moreover, no alteration was observed in cell area of hepatocytes or number of Kupffer cells. The fetuses had an increase in total number of hepatocytes and a reduction in the amount of megakaryocytes. These results show the hepatotoxic potential of usnic acid during pregnancy. However, its toxicity can be minimized by encapsulation in microspheres.